Epidemiological Study on Trichomonas Vaginalis Parasite and Estimation of Some Elements and Antioxidants in the Serum of Infected Women in Samarra City: Studi Epidemiologi Parasit Trichomonas Vaginalis dan Estimasi Beberapa Unsur dan Antioksidan dalam Serum Wanita Terinfeksi di Kota Samarra - Hamood , Nibras abud al Aziz (Universitas Muhammadiyah Sidoarjo, 2024)
The current study investigates the prevalence of Trichomonas vaginalis in women visiting Samarra General Hospital between August 2023 and June 2024. A total of 325 samples were examined from women aged 19 to 51 years, with an infection rate of 2.34%. The highest infection rate was observed in the 30-40 age group, among women experiencing itching during menstruation (4.16%), those with white vaginal discharge (2.97%), and infertile women (4.16%). The infection rate was higher among rural women (3.57%) compared to urban residents. Regarding trace elements, the study recorded a significant decrease in serum zinc and iron levels in infected women (p < 0.01) compared to the control group. However, no significant difference was observed in lead concentrations, with levels recorded as 2.83 µg/dl and 2.62 µg/dl in infected and control groups, respectively. Additionally, antioxidant levels showed a notable decline in infected women: Catalase (CAT): 6.88 pg/ml Superoxide dismutase (SOD): 15.31 pg/ml Glutathione peroxidase (GPx): 112.9 pg/ml Highlights: Prevalence: 2.34% infection in 325 women, highest in 30-40 age group. Trace Elements: Decreased zinc/iron, no significant lead difference. Antioxidants: Reduced CAT (6.88), SOD (15.31), GPx (112.9) pg/ml. Keywords: Trichomonas vaginalis, prevalence, trace elements, antioxidants, infection rate